Answer:
7/4 and 3
Step-by-step explanation:
Because all the other answers are a negative slope or undefined.
The graph shown is positive so the slope has to be positive.
Remember to press that Thanks button!
Answer:
The possible values of slope are 7/4 and 3.
Step-by-step explanation:
We need to find the possible values of slope of the given line.
The slope of an increasing line is positive.
The slope of a decreasing line is negative.
The slope of a vertical line is infinite.
The slope of a horizontal line is 0.
The given line is an increasing line because the value of y increases as x increases and vice versa.
So, the slope of given line must be positive.
Only 3 and 7/4 is positive.
Therefore, the possible values of slope are 7/4 and 3.
Draw a quick picture of 3 hundreds, 5 tens and 7 ones. What number does your quick picture show? Write in the three different ways
Answer:
The table represents the start of the division of
Step-by-step explanation: instgram mack.thrasher
In the figure attached, the quick picture can be seen. See the second picture for clarification.
Another way to represent that number is in a table format, as:
Hundreds tens ones
3 5 7
Finally, 3 hundreds 5 tens and 7 ones are equal to 300 + 50 + 7 = 357
Triangle J K L is shown. Angle J K L is a right angle. An altitude is drawn from point K to point M on side L J to form a right angle. The length of K M is 6 and the length of M J is 3. What is the length of line segment LJ? 9 units 12 units 15 units 18 units
Answer:
[tex]LJ=15\ units[/tex]
Step-by-step explanation:
see the attached figure to better understand the problem
step 1
Find the length side KJ
In the right triangle JKM
Applying the Pythagoras Theorem
[tex]KJ^{2}=JM^{2}+KM^{2}[/tex]
we have
[tex]JM=3\ units[/tex]
[tex]KM=6\ units[/tex]
substitute
[tex]KJ^{2}=3^{2}+6^{2}[/tex]
[tex]KJ^{2}=45}[/tex]
[tex]KJ=\sqrt{45}\ units[/tex]
simplify
[tex]KJ=3\sqrt{5}\ units[/tex]
step 2
Find the value of cosine of angle MJK in the right triangle JKM
[tex]cos(JKM)=JM/KJ[/tex]
substitute the values
[tex]cos(JKM)=\frac{3}{3\sqrt{5}}[/tex]
simplify
[tex]cos(JKM)=\frac{\sqrt{5}}{5}[/tex] -----> equation A
step 3
Find the value of cosine of angle MJK in the right triangle JKL
[tex]cos(JKM)=KJ/LJ[/tex]
we have
[tex]KJ=3\sqrt{5}\ units[/tex]
[tex]cos(JKM)=\frac{\sqrt{5}}{5}[/tex] ----> remember equation A
substitute the values
[tex]\frac{\sqrt{5}}{5}=\frac{3\sqrt{5}}{LJ}[/tex]
Simplify
[tex]LJ=5(3)=15\ units[/tex]
Answer:
The answer would be option C. 15 units :)
Step-by-step explanation:
Did it on edge :D
Hope this helps!
What is the solution to the equation 3/7(x+3)+5=3x+2?
Answer:
5/3
Step-by-step explanation:
i added a picture that will help you solve it.
The solution to the equation[tex]\dfrac{3}{7}(x+3)+5=3x+2[/tex] when "x" is an unknown variable is [tex]\dfrac{5}{3} .[/tex]
Two algebraic expressions separated by an equal symbol between them and with the same value are called equations.
Example = 2x +4 = 12
here, 4 and 12 are constants and x is variable.
To solve the equation[tex]\dfrac{3}{7}(x+3)+5=3x+2[/tex] we can follow these steps:
Multiply \dfrac{3}{7} into the brackets or inside the parentheses
[tex][\dfrac{3}{7}x + \dfrac{3}{7}\times3] + 5 = 3x + 2[/tex]
[tex]\dfrac{3}{7}x +\dfrac {9}{7} + 5 = 3x + 2[/tex]
On solving we get,
[tex]\dfrac{3x+9}{7} = 3x +2-5[/tex]
[tex]\dfrac{3x+9}{7} = 3x -3[/tex]
On cross multiplication we get,
[tex]{3x+9} = 7(3x -3)[/tex]
Opening the parenthesis we get
[tex]{3x+9} = (21x -21)[/tex]
Taking the variables to one side and constants on the right side we get,
[tex]{9+21} = (21x -3x)[/tex]
On further solving we get,
30 = 18 x
Simplify and solve for x:
Divide both sides by 18, and we get
[tex]\dfrac{30}{18} = x[/tex]
Now, in standard form
[tex]\dfrac{5}{3} = x[/tex]
In decimals, we get 1.66666.
Therefore, the solution to the equation [tex]\dfrac{3}{7}(x+3)+5=3x+2[/tex] is [tex]\dfrac{5}{3}[/tex].
Learn more about equations here :
https://brainly.com/question/14686792
#SPJ2
Write a system of equations and then solve for each variable.
3. The Arcadium arcade in Lynchburg, Tennessee uses 3 different colored tokens for their game machines. For
$20 you can purchase any of the following mixtures of tokens: 14 gold, 20 silver, and 24 bronze; OR, 20 gold, 15
silver, and 19 bronze; OR, 30 gold, 5 silver, and 13 bronze. What is the monetary value of each token?
Answer:
Gold=$0.5
Silver=$0.35
Bronze=$0.25
Step-by-step explanation:
This is the system of equations:
[tex]\$20=14G+20S+24B[/tex] (1)
[tex]\$20=20G+15S+19B[/tex] (2)
[tex]\$20=30G+5S+13B[/tex] (3)
Let's begin by substracting (2) from (1):
[tex]\left \{ {{\$20=14G+20S+24B} \atop {-\$20=-20G-15S-19B}} \right[/tex]
[tex]\$0=-6G+5S+5B[/tex] (4)
Isolating [tex]G[/tex] from (4):
[tex]G=\frac{5S+5B}{6}[/tex] (5)
Substituting (5) in (3):
[tex]\$20=30(\frac{5S+5B}{6})+5S+13B[/tex]
[tex]\$20=30S+38B[/tex] (6)
Substracting (3) from (2):
[tex]\left \{ {{\$20=20G+15S+19B} \atop {-\$20=-30G-5S-13B} \right[/tex]
[tex]\$0=-10G+10S=6B[/tex]
Isolating [tex]G[/tex]:
[tex]G=\frac{10S+6B}{10}[/tex] (7)
Making (5)=(7):
[tex]\frac{5S+5B}{6}=\frac{10S+6B}{10}[/tex]
Isolating [tex]B[/tex]:
[tex]B=\frac{5}{7}S[/tex] (8)
Substituting (8) in (6):
[tex]\$20=30S+38(\frac{5}{7}S)[/tex]
Isolating [tex]S[/tex]:
[tex]S=\$0.35[/tex] (9) This is the monetary value of silver token
Substituting (9) in (6):
[tex]\$20=30(\$0.35)+38B[/tex]
Finding [tex]B[/tex]:
[tex]B=\$0.25[/tex] (10) This is the monetary value of bronze token
Substituting (10) and (9) in (1):
[tex]\$20=14G+20(\$0.35)+24(\$0.25)[/tex]
Finding [tex]G[/tex]:
[tex]G=\$0.5[/tex] (11) This is the monetary value of golden token
ix is at least four more than a number. Which inequality represents this sentence? Question 20 options: a) 4 ≤ n + 6 b) 6 ≤ n + 4 c) 4 ≥ n + 6 d) 6 ≥ n + 4
Answer:
d) 6 ≥ n + 4
Step-by-step explanation:
Let n be the unknown number,
4 more than n = 4 + n
In inequality we use '≥' to represent greater than equal to or at least,
Thus,
Six is at least four more than a number.
⇒ 6 ≥ 4 more than n
⇒ 6 ≥ 4 + n
Which is the required inequality that represents the given statement,
OPTION d) is correct.
Answer:
b) 6 ≥ n + 4
Step-by-step explanation:
which is greater 8.2 or 8.23
8.23 because of you add 0 after the 8.2 that will make it 8.20.
Hope it makes sense :)
The cost to rent a car for a day is an initial cost of $35 and $0.25 per mile driven write an equation that represents to the cost of the car rental what is the total cost if you drove 250 miles
Answer:
$35 + $0.25m is the equation
If you drove 250 miles, it would cost $97.50
Step-by-step explanation:
250 * 0.25 = 62.5
62.5 + 35 = 97.5
What’s 1:6 equal too in two ways
Hey!
------------------------------------------------
Solution:
We can get two different ways of 1:6 by add +1:+6.
1 + 1 = 6 + 6
2:12
2 + 1 = 12 + 6
3:18
------------------------------------------------
Answer:
2:12 and 3:18
------------------------------------------------
Hope This Helped! Good Luck!
The difference of a number and 12 is 30
Answer:
42
Step-by-step explanation:
Difference is substitution, so a number (x) minus 12 equals 30
x-12=30
Add 12 to both sides
x=42
The problem statement is a Mathematics subtraction problem. It can be solved by setting up a simple equation n - 12 = 30, where 'n' is the unknown number. By solving the equation, we find n = 42.
Explanation:The subject of the problem statement 'The difference of a number and 12 is 30' lies in the Mathematics field. When the problem says the 'difference of a number and 12 is 30', it means we are dealing with a subtraction expression. Here, we can write a simple equation to solve this. If we use 'n' to represent the unknown number, the equation will be: n - 12 = 30. To solve for n, we should add 12 to both sides of the equation to balance it. So, it will be n = 30 + 12, and hence n = 42. So, the number in the problem statement is 42.
Learn more about Subtraction here:https://brainly.com/question/20438352
#SPJ2
Lucy ate eight more than three times as many pretzels as Matt Lucy ate 56 pretzels how many pretzels did Matt eat
Lucy ate 56 pretzels and Matt ate 16 pretzels.
Explanation:To find out how many pretzels Matt ate, we need to use the information given in the question. Let's represent the number of pretzels Matt ate as 'x'. According to the question, Lucy ate 56 pretzels, which is 8 more than three times the number of pretzels Matt ate. So we can write the equation: 56 = 3x + 8. We must place x on one side of the equation alone in order to solve for it. Subtracting 8 from both sides, we get 56 - 8 = 3x, which simplifies to 48 = 3x. Finally, dividing both sides by 3, we find that x = 16.
Learn more about Number of pretzels eaten by Lucy and Matt here:https://brainly.com/question/32284278
#SPJ2
Which of the following values is the solution to the equation -35x = -105 ? 3 -3
Answer:
3.
Step-by-step explanation:
-35x = -105
Divide both sides by -35:
x = -105/-35
= 3.
The solution to the equation is x = 3.
What is an equation?Two or more expressions with an equal sign are defined as an equation.
The given equation is -35x = -105.
Solve the equation as follows:
-35x = -105
35x = 105
x = 105/35
x = 3
Hence, the solution to the equation is x = 3.
Learn more about equations here:
https://brainly.com/question/10413253
#SPJ2
solve this problem y=(x-3)^2 when x=9
Solve for p.
11p − 2p + 4 = 13
p =
Answer:
p = 1
Step-by-step explanation:
11p - 2p + 4 = 13
9p + 4 = 13
- 4 -4
9p = 9
9p/9 = p
9/9 = 1
Answer:
p=1
Step-by-step explanation:
11×1=11
2×1=2
11-2=9
9+4=13
Solve 6+2x^2-3x=8x^2
Answer: 6x^2+3x-6
Step-by-step explanation:
6+2x^2-3x=8x^2
-2x^2. -2x^2
6-3x=6x^2
= 6x^2+3x-6
Answer:
Step-by-step explanation:
Please put these from greatest to least.
2.485
2.463
2.90
hope this helps
Answer:
2.90, 2.463, 2.485
Step-by-step explanation:
I'm pretty sure when you do this you need to find the number that's closest to one (2.90). The bigger the number the less it's closer to one. If that makes sense.
I'm pretty sure I did this right. If i'm wrong I do apologize.
(I haven't done greatest to least for decimals in awhile. So seriously i'm sorry if this is wrong)
‼️‼️solve by substitution {2p-3r=6
{-2p+3r=-6 all these problems w work shown r due in the morning pls help !!
Answer:
#7: (p, r) = (0, -2) #8: (z,w) = z, [tex]\frac{8}{3}[/tex] + [tex]\frac{4}{3}[/tex]z), ∈R #9: (c,d) = (3,3) #10: (u,x) ∈∅ #11: (a,b) = (-1, 2) #12:
Step-by-step explanation:
#7
Solve for 2p
2p - 3r = 6
2p = -6 -3r
substitute the given value of 2p into equation 2p - 3r = 6
-6 - 3r - 3r = 6
solve for r
r= -2
substitute value of r in equation
2p = -6 - 3x (-2)
solve for p
p=0
solution is ordered pair (p,r) = (0, -2)
#8
Solve for w
w= [tex]\frac{8}{3}[/tex] + [tex]\frac{4}{3}[/tex]z
substitute the given value of w into equation
6 ([tex]\frac{8}{3}[/tex] + [tex]\frac{4}{3}[/tex]z) - 8z = 16
solve for z
z ∈ R
The statement is true for any value of z and w that satisfy both equations from the system. Therefore, the solution is in parametric form.
(z,w) = z, [tex]\frac{8}{3}[/tex] + [tex]\frac{4}{3}[/tex]z)
#9
Solve for c
c + d = 6
c = d
substitute the given value of c into equation c + d = 6
d + d = 6
solve for d
d=3
substitute value of d in equation
c=3
solution is ordered pair (c,d) = (3,3)
#10
Solve for u
u= 3-2x
substitute the given value of c into equation
2 (3-2x) +4x = -6
solve for x
x ∈∅
Since the system has no solution for x the answer is
(u,x) ∈∅
#11
Solve for b
b= 5+3a
substitute the value of b into equation
3a + 5 + 3a+ b = -1
solve for a
a= -1
substitute the value of a into equation
b= 5 + 3x (-1)
solve for b
b=2
solution is ordered pair (a, b) = (-1, 2)
Final answer:
The system of equations leads to a true statement when added together, indicating that the two equations represent the same line and thus have infinitely many solutions. There's no unique solution for the variables but rather a relationship where each value of p corresponds to a specific value of r.
Explanation:
To solve the system of equations by substitution, let's first identify the given equations and the unknown variables. The two given equations are 2p - 3r = 6 and -2p + 3r = -6. We need to solve for the unknown variables p and r. Notice that adding these two equations together will eliminate both p and r, giving us an identity 0 = 0, which indicates the system has infinitely many solutions or the equations represent the same line.
Here's the process to verify this:
First equation: 2p - 3r = 6
Second equation: -2p + 3r = -6
Add the two equations: (2p - 3r) + (-2p + 3r) = 6 - 6
This simplifies to: 0 = 0
Since we have derived a true statement that does not involve the variables p and r, it is clear that these two equations are dependent and represent the same line. Therefore, there isn't a unique solution for p and r, but rather an infinite number of solutions where each value of p corresponds to a specific value of r that will satisfy both equations.
To check if the answer is reasonable, we can take any point that lies on this line and see if it satisfies both original equations, confirming that it is indeed a solution.
How do I get from this guy 3/2/(15/4) to 2/5?
[tex]\bf \cfrac{~~\frac{3}{2}~~}{\frac{15}{4}}\implies \cfrac{~~\begin{matrix} 3 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{~~\begin{matrix}2 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\cdot \cfrac{\stackrel{2}{~~\begin{matrix} 4 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}{\underset{5}{~~\begin{matrix} 15 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}\implies \cfrac{2}{5}[/tex]
To simplify the expression 3/2/(15/4), first convert the division of fractions to multiplication by the reciprocal, giving (3/2) * (4/15). Multiply the numerators and denominators and then reduce the fraction by dividing both by their greatest common divisor. The simplified result is 2/5.
To simplify the expression 3/2/(15/4), you would follow these steps:
Understand that dividing by a fraction is the same as multiplying by its reciprocal. In this case, 15/4 is the divisor, so we take its reciprocal which is 4/15.Multiply the original fraction 3/2 by the reciprocal of 15/4 which is 4/15.Perform the multiplication: (3/2) * (4/15).First, simplify by multiplying the numerators together and the denominators together: 3 * 4 = 12 and 2 * 15 = 30.So, you have 12/30, which can be reduced. Divide both the numerator and denominator by their greatest common divisor (GCD), which is 6.12 / 6 = 2 and 30 / 6 = 5, therefore the fraction simplifies to 2/5.Following these steps results in the original expression 3/2/(15/4) simplifying to 2/5.
solve for x 2/x+1/2=3/4
Identify the rule for the following pattern:
99, 90, 81...
1. Change the following subtraction problems into addition problems.
a. -2-3
b. 8-(-1)
C. 4-9
Answer:
a. -2 + (-3)
b. 8 + 1
c. 4 + (-9)
Final answer:
The given subtraction problems can be changed to addition like -2-3 becomes -2+(-3), 8-(-1) becomes 8+1, and 4-9 becomes 4+(-9).
Explanation:
To change a subtraction problem into an addition problem, you can apply the concept that subtracting a number is equivalent to adding its opposite. This principle can be used to transform the given subtraction expressions into addition expressions as follows:
-2 - 3 is equivalent to -2 + (-3)
8 - (-1) is equivalent to 8 + 1 because subtracting a negative is like adding a positive.
4 - 9 is equivalent to 4 + (-9)
When adding numbers, follow these rules depending on the signs:
When two positive numbers are added, the result is positive (3 + 2 = 5).
When two negative numbers are added, the result is negative (-4 + (-2) = -6).
When adding numbers with opposite signs, subtract the smaller number from the larger one, and the result takes the sign of the larger number (-5 + 3 = -2).
Sketch a cube with 3 cm
Answer:
Step-by-step explanation: is This what you want?
positive whole numbers less than 9
4 can be one too because its less than 9 and its a whole number
Hope it helps :)
4. Thirty divided by seven times a number
A. 30 + 7n
B. in
30
30(7n)
None of the above
30:7.
Answer:
30/7n
Step-by-step explanation:
let n be the no.
seven times a no. is 7n
so ans is 30/7n
Find x please!!!!!!!!!
Evaluate this exponential expression.
4. (2 + 5)2 - 52 =
A. 46
B. 144
c. 8
D. 171
Answer:
B
Step-by-step explanation:
Given
4(2 + 5)² - 52
Evaluate the parenthesis
4 × 7² - 52 ← evaluate the exponent
4 × 49 - 52 ← evaluate the multiplication
= 196 - 52 ← evaluate the subtraction
= 144 → B
Answer: D 171
Step-by-step explanation:
Simplify: 7 exponent9 7 exponent3
Answer:
7^9= 40,353,607
7*7*7*7*7*7*7*7*7=40,353,607
7^3 =343
7*7*7=343
What is the slope of the line passing through the points
(-1,7) and (4,-1)
Answer:
(5 , -18)
Hope this helps.
From your vro Que
Answer: [tex]\dfrac{-8}{5}[/tex]
Step-by-step explanation:
The slope of a line passing through points (a,b) and (m,n) is given by :-
[tex]\text{Slope}=\dfrac{n-b}{m-a}[/tex]
Given points : (-1,7) and (4,-1)
Then, the slope of the line passing through the points (-1,7) and (4,-1) will be :-
[tex]\text{Slope}=\dfrac{-1-7}{4-(-1)}\\\\=\dfrac{-8}{4+1}\\\\=\dfrac{-8}{5}[/tex]
Hence, the required slope = [tex]\dfrac{-8}{5}[/tex]
What is the range of the function on the graph
Answer:
Y ≤ 3
Step-by-step explanation:
The Domain is the x values the function holds, while the range is the y values the function holds. This means that, looking at the graph, the range of the function is all y values less than or equal to 3, or Y ≤ 3.
write an equation for the line parallel to y= -2x+1 that contains (-2,5)
Answer:
y = - 2x + 1
Step-by-step explanation:
Parallels line have the same slope, when an equation is in the form y= mx + b, m is the slope. In this problem slope = - 2
Now with the slope what is missing is the y-intercept, the problem says that the line contains the point (-2, 5), replacing that point in the equation you can solve it to find the y-intercept
y = mx + b
5 = (-2)(-2) + b
5 = 4 + b
1 + b
y = - 2x +1
Two parallel lines are intersected by a third line so that angles 1 and 5 are congruent. 2 parallel horizontal lines are intersected by a third line. On the first horizontal line where the third line intersects, 4 angles are created. Labeled clockwise, from uppercase left, the angles are 1, 2, 4, 3. On the second horizontal line, where the third line intersects, 4 angles are created. Labeled clockwise, from uppercase left, the angles are 5, 6, blank, blank. Which statement is true about angles 3 and 5? They are acute. They are congruent. They are complementary. They are supplementary.
Answer:
"They are supplementary" ⇒ last answer
Step-by-step explanation:
* Look to the attached figure
- Two parallel horizontal lines are intersected by a third line
- The angles formed form intersection are labeled on the figure
- From the two parallel lines and
∠5 ≅ ∠1 ⇒ corresponding angles
m∠5 = m∠1
- A linear pair is two angles that are adjacent and form a line and
they are supplementary
∠1 and ∠3 form a line
∠1 and ∠3 are linear pair
* lets prove that ∠3 and ∠5 are supplementary
∵ m∠1 = m∠5 ⇒ corresponding angles
∵ ∠1 and ∠3 form a linear pair
∵ Linear pair are supplementary
∴ m∠1 + m∠3 = 180°
- By substitute ∠1 by ∠5
∴ m∠5 + m∠3 = 180
∴ ∠5 and ∠3 are supplementary
* The true statement is "They are supplementary"
Angles 3 and 5 are congruent because they are alternate interior angles formed by a transversal intersecting two parallel lines. This is supported by the Alternate Interior Angles Theorem.
To determine the relationship between angles 3 and 5 when two parallel lines are intersected by a transversal, we can use the properties of alternate interior angles.
Given that angles 1 and 5 are congruent, we identify that they are alternate interior angles formed by the transversal intersecting two parallel lines. By the Alternate Interior Angles Theorem, since the lines are parallel, angles 1 and 5 are congruent.Angles 3 and 5 in this setup are also alternate interior angles, and by the same theorem, they are congruent.
This leads us to the conclusion that:
Angles 3 and 5 are congruent.